2017
DOI: 10.1111/echo.13519
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of blood flow through intrapulmonary arteriovenous anastomoses and patent foramen ovale at rest and during exercise in stroke and transient ischemic attack patients

Abstract: Novel genetic predispositions reported here in PFO subjects should be investigated further in larger stroke and/or TIA patient datasets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…The key interpretive points for TTCE include: • TTCE is considered positive for intrapulmonary rightto-left shunting if microbubbles appear in the left atrium after a delay (usually 3-4 cardiac cycles is considered a cutoff) or ramp in intensity (in contrast to intracardiac shunts); the intrapulmonary shunt origin is certain if the bubble density is greater in the left heart than in the right, often requiring 30-60 s of recording [72] • PAVMs are one cause of intrapulmonary right-to-left shunting; intrapulmonary shunting demonstrable by TTCE is also evident in ∼ 10% of the general population at rest, and the majority of healthy individuals on exercise, and/or after adrenergic stimuli [22,73,74] • A positive intrapulmonary shunt study is also more likely after injury to the delicate pulmonary capillaries, for example, following a second injection of contrast medium [72] • TTCE is usually positive in HHT1 patients (85%) [21] , and often positive in HHT2 patients (35%) [21] ; semiquantification of the shunt may help distinguish from physiological shunting and enhance the positive predictive value for a PAVM amenable to treatment [75] or complication risk [76] • In the absence of PAVMs visible on CT scan, a contrast echocardiogram demonstrating an intrapulmonary shunt does not appear to be associated with an enhanced neurological risk in HHT patients [76] ; TTCE is therefore not indicated when the presence of a PAVM has already been established by CT or during follow-up of patients with treated PAVMs; there are also reassuring data for the general population indicating that very few exercise-induced arterialized gas bubbles reach the cerebral vasculature [77] , although it is not clear that the same applies to nongaseous paradoxical emboli Different algorithms have been proposed for the screening and follow-up of adult patients with HHT according to the degree of local expertise with CE ( Fig. 3 ).…”
Section: Screening For Pavms In the Hht Populationmentioning
confidence: 99%
“…The key interpretive points for TTCE include: • TTCE is considered positive for intrapulmonary rightto-left shunting if microbubbles appear in the left atrium after a delay (usually 3-4 cardiac cycles is considered a cutoff) or ramp in intensity (in contrast to intracardiac shunts); the intrapulmonary shunt origin is certain if the bubble density is greater in the left heart than in the right, often requiring 30-60 s of recording [72] • PAVMs are one cause of intrapulmonary right-to-left shunting; intrapulmonary shunting demonstrable by TTCE is also evident in ∼ 10% of the general population at rest, and the majority of healthy individuals on exercise, and/or after adrenergic stimuli [22,73,74] • A positive intrapulmonary shunt study is also more likely after injury to the delicate pulmonary capillaries, for example, following a second injection of contrast medium [72] • TTCE is usually positive in HHT1 patients (85%) [21] , and often positive in HHT2 patients (35%) [21] ; semiquantification of the shunt may help distinguish from physiological shunting and enhance the positive predictive value for a PAVM amenable to treatment [75] or complication risk [76] • In the absence of PAVMs visible on CT scan, a contrast echocardiogram demonstrating an intrapulmonary shunt does not appear to be associated with an enhanced neurological risk in HHT patients [76] ; TTCE is therefore not indicated when the presence of a PAVM has already been established by CT or during follow-up of patients with treated PAVMs; there are also reassuring data for the general population indicating that very few exercise-induced arterialized gas bubbles reach the cerebral vasculature [77] , although it is not clear that the same applies to nongaseous paradoxical emboli Different algorithms have been proposed for the screening and follow-up of adult patients with HHT according to the degree of local expertise with CE ( Fig. 3 ).…”
Section: Screening For Pavms In the Hht Populationmentioning
confidence: 99%
“…Radiological differential diagnoses of a PAVM include a bronchocoele, bronchopulmonary sequestration, pulmonary varix, pulmonary arterial aneurysm and aberrant systemic to pulmonary communications 2. Other causes of right-to-left shunts detectable by contrast echocardiography include intermittent shunting through intracardiac defects (when right-side pressures exceed left, most commonly after a Valsalva manoeuvre61), the hepatopulmonary syndrome62 and functional shunting (present in ~10% of the general population at rest, rising on exercise,63 after adrenergic stimuli64 and in response to low PaO 2 65). …”
Section: Introductionmentioning
confidence: 99%
“…The relationship between IPAVAs and stroke still remains questionable. Tobin et al and Rapp et al have proposed IPAVAs as a possible mechanism of stroke based on necropsy and animal experiments, while some scholars suggested IPAVAs are not considered eligible for thrombus passage causing the stroke ( 10 , 29 ). In our study, the incidence of P-RLS could be as high as 79.2% in patients without PFO and 41.6% of them with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of PAVMs in the population is 2–3/100,000 ( 9 ), therefore, the study of P-RLS has been neglected. In recent years, some studies showed that P-RLS is a potential facilitator of stroke; at the same time, there is indeed a problem that P-RLS is regarded as PFO-RLS leading to overtreatment of PFO, they all remind us that P-RLS should not be ignored, IPAVAs in particular ( 10 12 ). In this study, we used contrast transesophageal echocardiography (c-TEE) and contrast transthoracic echocardiography (c-TTE) to compare P-RLS and PFO-RLS in order to investigate the characteristics of P-RLS and the relationship between P-RLS and PFO-RLS, hoping to provide new ideas and references for clinical follow-up studies and management disposal decisions of PFO.…”
Section: Introductionmentioning
confidence: 99%